Facile Investigation of Ti3+ State in Ti-based Ziegler-Natta Catalyst with A Combination of Cocatalysts Using Electron Spin Resonance (ESR) - Thanyaporn Pongchan; Piyasan Praserthdam; Bunjerd Jongsomjit (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
This study aims to investigate the influences of a combination of cocatalysts including triethylaluminum (TEA) and tri-n-octylaluminum (TnOA) for activation of a commercial Ti-based Ziegler-Natta catalyst during ethylene polymerization and ethylene/1-hexene copolymerization on the change in Ti3+ during polymerization. Thus, electron spin resonance (ESR) technique was performed to monitor the change in Ti3+ depending on the catalyst activation by a single and combination of cocatalyst. It revealed that the amount of Ti3+ played a crucial role on both ethylene polymerization and ethylene/1-hexene copolymerization. For ethylene polymerization, the activation with TEA apparently resulted in the highest catalytic activity. The activation with TEA+TnOA combination exhibited a moderate activity, whereas TnOA activation gave the lowest activity. In case of ethylene/1-hexene copolymerization, it revealed that the presence of 1-hexene decreased activity. The effect of different cocatalysts tended to be similar to the one in the absence of 1-hexene. The decrease of temperature from 80 to 70 °C in ethylene/1-hexene copolymerization tended to lower catalytic activity for TnOA and TEA+TnOA, whereas only slight effect was observed for TEA system. The effect of different cocatalyst activation on the change of Ti3+ state of catalyst was elucidated by ESR measurement. It appeared that the activation of catalyst with TEA+TnOA combination essentially inhibited the reduction of Ti3+ to Ti2+ leading to lower activity.  Furthermore, the polymer properties such as morphology and crystallinity can be altered by different cocatalysts. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).